Modules of interaction for ASD children using rero robot (Humanoid) - Ishak, Nor Izzati; Md. Yusof, Hazlina; Ramlee, Mohd Rais Hakim; Sidek, Shahrul Na'im; Rusli, Nazreen (IEEE, 2020)
Autism Spectrum Disorder (ASD) is a neurological and developmental disorder that affects one's ability to understand social cues and to communicate. As it begins early in childhood and can last throughout a person's life, it is important to have an early intervention and rehabilitation. Previous research has shown that robotic platforms helped and encouraged positive outcome in ASD children rehabilitation. Early interventions through human-robot interaction (HRI) have the potential when used to improve communication and social skills of the children. In this research, a new framework has been developed featuring a robot and human interaction modules. A commercial robot, Rero has been adopted and used as the interaction medium. This robot has been selected based on its reconfigurable capability and ability to be developed into many forms. It is also mobile, speech enabled, controllable, programmable, and attractive. Five modules of interaction have been developed and approval from special education teachers and therapists has been sought. The modules are created to help the children to be able to imitate actions, follow instructions, name objects, as well as to focus and match colours. Observations from the experiment shows that the children enjoyed the interaction modules with a median of more than 70% of scores and were well engaged with the robots with certain type of modules.